Dietary Effects of Fasting on the Lipid Panel - Hourizadeh, Jason; Munshi, Rezwan; Zeltser, Roman; Makaryus, Amgad N. (Current Cardiology Reviews, 2024)
Introduction: Dietary habits, such as the Mediterranean diet and the Dietary Approaches to Stop Hypertension (DASH), have been shown to improve cardiac health. Another more recent popular form of dieting incorporates periods of fasting known as intermittent fasting. The two main forms are alternate-day fasting and time-restricted eating. Methods: PubMed search and literature review was undertaken. This review evaluates the current literature regarding the effects of the fasting dietary model and other types of fasting upon the lipid panel. Results: There have been studies that have shown that intermittent fasting does provide a benefit in cardiovascular health, weight loss, and hypertension. However, the effect on cholesterol and triglyceride levels during intermittent fasting is in question. Conclusion: The effect that fasting has on one’s lipid panel is unclear, there are studies that show that different forms of fasting affect the lipid panel in various ways. There are studies that show that intermittent fasting does improve one’s lipid profile and provides health benefits. Randomized controlled clinical trials with a large sample size are needed to evaluate the effects that intermittent fasting has based on race, ethnicity, gender, obesity, dyslipidemia, diabetic and healthy patients, and will lead to definitive evidence of lipid panel outcomes beyond current evidence based solely upon observational cohorts with numerous and multifactorial confounding factors and biases.
Keywords: Cholesterol